Analisis Dampak Penerapan Kebijakan Bonded Warehouse (Gudang Berikat) Terhadap Biaya Logistik Di Pelabuhan - Sapit Hidayat; Habibi Palippui (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2020)
A bonded warehouse is a place to store imported goods, which can be accompanied by one or more activities in the form of packaging / repacking, sorting, merging (kitting), packing, adjusting, cutting, for certain goods within a certain period to be reissued. In the Minister of Finance Regulation (PMK) No.155 / PMK.04 / 2019 concerning Bonded Warehouses, the Ministry of Finance emphasizes that this tightening of supervision is carried out in two forms, both in terms of taxation and the mechanism for importing goods. This bonded warehouse policy is expected to reduce national logistics costs by reducing dwelling time at ports and accelerating access to raw material warehouses to industry. The essence of this study is to analyze the extent of the influence obtained by users of bonded warehouse services in terms of logistics costs. Cost comparisons are obtained from surveys with companies that have already utilized bonded warehouse facilities.